Determination of Hydrocarbon Zones Using Logging Data Analysis in A Sandstone Reservoir (Case Study: Structure ‘TL’ Basin North West Java) - Herianto, Herianto (Indonesian Journal on Geoscience, 2018)
DOI: 10.17014/ijog.5.3.251-263Northwest Java Basin is one of the Indonesian basins that has the potential of hydrocarbon reservoir. A petrophysical analysis plays a role in determining the physical properties of reservoir rocks such as shale volume, porosity, and water saturation zones which is to analyze the hydrocarbon zone possibilities (net pay). A qualitative analysis and correlation of rock lithology study were carried out at seven wells, while a quantitative study was performed by calculating the volume of the shale with a linear method, density-neutron porosity, and water saturation using simandoux equation, then zoning the prospect zones was finally done. Based on the calculation and data analysis, Vsh cutoff value obtained is 23%, the porosity is 10.6%, and water saturation is 71%. Then, the zones of hydrocarbon prospects were recovered, that are the PI-08 wells (9.632 ft - 9.662 ft), PI-10 (9.420 ft - 9.468 ft, 9.475 ft - 9.516 ft, 10.155 ft - 10.175 ft), well PI-11 (9.268 ft - 9.288 ft), well PI-11ST (9.268 ft - 9.927 ft), well PI-12 (9.396 ft - 9.461 ft, 10.047 ft - 10.059 ft), and PI-13 wells (9.356 ft - 9.416 ft, 9.980 ft - 10.000 ft).